Perovskite–Nitrogen‐Doped Carbon Nanotube Composite as Bifunctional Catalysts for Rechargeable Lithium–Air Batteries. Issue 6 (13th February 2015) - Park, Hey Woong; Lee, Dong Un; Park, Moon Gyu; Ahmed, Raihan; Seo, Min Ho; Nazar, Linda F.; Chen, Zhongwei
Abstract Developing an effective bifunctional catalyst is a significant issue, as rechargeable metal–air batteries are very attractive for future energy systems. In this study, a facile one‐pot process is introduced to prepare an advanced bifunctional catalyst (op‐LN) incorporating nitrogen‐doped carbon nanotubes (NCNTs) into perovskite La0.5Sr0.5Co0.8Fe0.2O3 nanoparticles (LSCF‐NPs). Confirmed by half‐cell testing, op‐LN exhibits synergistic effects of LSCF‐NP and NCNT with excellent bifunctionality for both the oxygen reduction reaction and the oxygen evolution reaction. Furthermore, op‐LN exhibits comparable performances in these reactions to Pt/C and Ir/C, respectively, which highlights its potential for use as a commercially viable bifunctional catalyst. Moreover, the results obtained by testing op‐LN in a practical Li–air battery demonstrate improved and complementary charge/discharge performance compared to those of LSCF‐NP and NCNT, and this confirms that simply prepared op‐LN is a promising candidate as a highly effective bifunctional catalyst for rechargeable metal–air batteries.